The synthesis of 2- and 3-substituted indoles - Leboho, Tlabo Caiphus (My University, 2009)
One of the main groups of organic compounds containing nitrogen in both cyclic systems and straight chains is the alkaloids. Indole is perhaps the single most common heterocycle in all of chemistry and it is embodied in a myriad of natural products, pharmaceutical agents and a growing list of polymers. This dissertation presents method for the synthesis of substituted indoles bearing aryl substituents onto the 2- and 3- position as well as 2,3-fused indoles. The route for the synthesis of the aryl substituted indoles starts from the indole nucleus which was protected using the phenylsulfonyl group because it was found that the group is easy to remove and does not require harsh conditions. After successful protection of the indole nucleus NH as Nphenylsulfonyl, bromine was introduced at the 3-position of the indole nucleus while iodine was introduced at the 2-position of the indole nucleus. The bromination of the indole nucleus was not easily achieved because the reaction of molecular bromine with indole resulted in the formation of 2,3-dibromoindole while activated 5-methoxyindole gave an insoluble 2,3,4-tribromoindole. However, this problem was solved by refluxing indole with molecular bromine in the presence of sodium methoxide while activated 5-methoxyindole was refluxed with N-bromosuccinimide in the presence of catalytic benzoyl peroxide. 2-Iodoindoles were synthesized using directed ortho metallation, where isopropyl magnesium chloride was used in the presence of catalytic amount of diisopropylamine. Using standard aqueous Suzuki-Miyaura cross-coupling in the presence of sodium carbonate as a base, 2-aryl, 3-aryl as well as 2,3-diaryl substituted indoles were synthesized in good to excellent yields. The synthesis of 2,3-fused indoles was achieved in poor yields starting from 1-(phenylsulfonyl)indole which was alkylated using allyl bromide at the 2- position and formylated at the 3-position of the indole nucleus to the cyclization of the alcohols using mercury acetate.